Alteration of Coral Reef Community Structure Caused by Athropogenic Activity in the Coastal Area of Giliketapang Island, Probolinggo, East Java, Indonesia - Lutfiatul Puspitasari; Setijono Samino; Catur Retnaningdyah (Journal of Tropical Life Science, 2013)
The aim of the research was to know the effect of anthropogenic activity around the coastal area of Giliketapang Island toward community structure of coral reefs. This study used belt transect method which consisted of 18 transects in three locations (harbour, near the forest, and transitionol areas) at 50-80 m from the coast, with a plot sized of 2×2m2. Abundance of coral reefs were observed based on their coverage. There were 11 families of coral reefs found. The percentage of coral damage decreased and the number of the species increased at the zones far from the coast. This also affected the coverage value of coral reefs. Coral coverage at the harbour and near the forest was 53. 06 % and 65. 36 % respectively, whereas in the transitional area was 38. 38%. Co-domination between Porites lobata and Chyphastrea microphthalma occurred at the harbour, while Poritesmayeri and Acropora spp. co-dominated in the location near the forest. Poritidae family dominated the transition area. Anthropogenic activities at transitional location caused severe damage toward coral reefs.